Separation of Acearylenes from High-Temperature Coal Tar - 周建石 马全领 宗志敏 魏贤勇 (Transactions of Tianjin University, 2012)
High-temperature coal tar was extracted with petroleum ether （PE） under ultrasonic irradiation and the extracts were analyzed with gas chromatograph/mass spectrometer. The acearylene fractions including acenaphthylene, aceanthrylene and cyclopentapyrene were enriched together and named E, which was then transferred to a car- tridge in Isolera-One flash chromatography. Three groups of compounds were eluted out with ethyl acetate/PE mixed solvent （volume ratio 1：9） and named E1, E2 and E3 according to their main components. Acenaphthylene accounted for 78.2% in El, aceanthrylene 71.6% in E2 and cyclopentapyrene 75.9% in E3, respectively. The three groups of acearylenes were purified by Sephadex LH-20 column chromatography with ethanol/cyclohexane mixed solvent （vol- ume ratio 1：4）, and then confirmed with nuclear magnetic resonance spectrometer. This method indicates that flash chromatography has a good effect on separating the compounds with a similar structnre after extraction under ultrasonic irradiation.